THE USE OF MEMRISE APPLICATION TO INCREASE STUDENTS’ ENGLISH VOCABULARY MASTERY AT MTsN 2 KOTA MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2026)
This study investigates the effectiveness of the Memrise application in enhancing students' mastery of English vocabulary. Conducted at MTsN 2 Kota Makassar, the research aims to assess the impact of digital learning tools on language acquisition among seventh-grade students. Utilizing a mixed-methods approach, the study involved pre-tests and post-tests to evaluate vocabulary improvement, alongside questionnaires to gauge student engagement and motivation. The findings indicate that the Memrise application significantly improves vocabulary retention and usage, fostering a more interactive and enjoyable learning environment. The results underscore the potential of integrating technology into language education to support traditional teaching methods. This research contributes to the growing body of evidence supporting the use of educational technology in classrooms and offers practical insights for educators seeking to enhance vocabulary learning through digital platforms.